2019
DOI: 10.1097/md.0000000000016207
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin expression and its prognostic role according to microsatellite instability status in colorectal adenocarcinoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…In contrast, the present study used MN-1 antibody, which has a higher affinity and positivity (% positive cells in immunohistochemistry) than 5B2 (11,24). Kim et al reported the prognostic role of MSLN in microsatellite unstable CRCs using SP74 antibody (17); however, this type of association was not confirmed in our cohort (data not shown). The discrepancies in these studies might result from the patient cohort (patient number and pathological stage) as well as the anti-MSLN antibody used.…”
Section: Msln Expression --------------------------------------------contrasting
confidence: 64%
See 2 more Smart Citations
“…In contrast, the present study used MN-1 antibody, which has a higher affinity and positivity (% positive cells in immunohistochemistry) than 5B2 (11,24). Kim et al reported the prognostic role of MSLN in microsatellite unstable CRCs using SP74 antibody (17); however, this type of association was not confirmed in our cohort (data not shown). The discrepancies in these studies might result from the patient cohort (patient number and pathological stage) as well as the anti-MSLN antibody used.…”
Section: Msln Expression --------------------------------------------contrasting
confidence: 64%
“…The present study analyzed the impact of diffuse MSLN expression on the survival of stage II to IV CRC patients and determined its expression as a potential independent risk factor (HR, 2.26; 95% CI, 1.04-4.91; P= 0.039). Several studies have analyzed the impact of tumor MSLN expression on the survival of CRC patients (15)(16)(17). Shiraishi et al (15) found an adverse impact of MSLN expression on the survival of stage II/III CRC patients with statistical significance; however, Kawamata et al (16), found no significant difference in stage I to IV patients.…”
Section: Msln Expression --------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane MSLN staining was performed by a trained pathologist. The staining intensity for evaluating MSLN protein expression was recorded using a four-tiered scoring system (0: no detectable signal, 1 + : weak, 2 + : moderate, and 3 + : strong), which is described in the antibody kit's instructions and previous reports using the same clone of the anti-MSLN antibody [ 18 20 ]. In addition, we used a quantitative analysis of IHC (H-Score) for a more detailed evaluation of the expression status.…”
Section: Methodsmentioning
confidence: 99%
“…Microsatellites are short tandem repeats that are found throughout the human genome [ 39 ]. Compared with normal tissue, the microsatellite of tumor tissue changes the length of the microsatellite due to the insertion or deletion of repeating units, called microsatellite instability (MSI) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%